2020
DOI: 10.1371/journal.pone.0232000
|View full text |Cite
|
Sign up to set email alerts
|

Association between the school environment and children’s body mass index in Terengganu: A cross sectional study

Abstract: With the ongoing interest in implementing school policies to address the problem of childhood obesity in Malaysia, there is urgent need for information about the association between school environment and children's weight status. This study aims to investigate the association between school environmental factors (physical, economic, political and sociocultural) with BMI of school children in Terengganu. The school environment factors were assessed using a set of validated whole-school environmental mapping qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
(40 reference statements)
1
8
0
4
Order By: Relevance
“…32 The results of this study also showed that there was a relationship between physical activity and BMI; this is in line with the previous study showing the same results. 34 A less diverse diet consisting of plant-based food sources but low in fruit and vegetable sources is one of the major nutritional problems in the diets of developing countries. 35 The results of this study showed that there was no relationship between dietary diversity and nutritional status; this is not in line with the previous studies stating that better dietary diversity is related to the nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…32 The results of this study also showed that there was a relationship between physical activity and BMI; this is in line with the previous study showing the same results. 34 A less diverse diet consisting of plant-based food sources but low in fruit and vegetable sources is one of the major nutritional problems in the diets of developing countries. 35 The results of this study showed that there was no relationship between dietary diversity and nutritional status; this is not in line with the previous studies stating that better dietary diversity is related to the nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…En comparación con las cifras nacionales 10 , el porcentaje que cumple con las recomendaciones de consumo de comida rápida y de frutas fue mayor, mientras que la prevalencia de obesidad fue ligeramente menor. Si bien son múltiples los factores de riesgo asociados al aumento en la prevalencia de obesidad 6 , estas diferencias pueden ser atribuidas a entornos escolares que promueven y facilitan elecciones saludables, y que involucran la escuela, la familia y la comunidad 4 Nuestros resultados evidenciaron que los adolescentes con obesidad y con hábitos alimentarios inadecuados tienen una CVRS significativamente menor que sus pares no obesos y con hábitos alimentarios saludables. Se observó que los adolescentes con obesidad y con consumo inadecuado de frutas reportaron una peor percepción de la dimensión bienestar físico.…”
Section: Discussionunclassified
“…fabiola.vilugron@upla.cl L os hábitos alimentarios han sido definidos como "los patrones conductuales regulares que son observados en algunas especies de interés, y que consta de formas en las cuales sus miembros se procuran el sustento nutritivo, especialmente el tipo de alimento que se ingiere y cómo se ingiere" 1 . La adolescencia se considera una etapa nutricionalmente vulnerable debido a que los hábitos alimentarios están fuertemente influenciados por factores socioculturales, emocionales y conductuales, que ocurren en el contexto y que pueden provocar o reforzar el consumo excesivo de alimentos no nutritivos [2][3][4] . La causa principal de la obesidad es el desequilibrio entre la ingesta alimentaria y la actividad física.…”
unclassified
“…This is especially important as most findings presented above follow a social gradient with positive associations between health behaviour, health literacy and family affluence [ 6 , 7 , 8 ]. Third, schools are not merely access points to children and young people, but also have an influence on health and health behaviour through their structures, conditions and processes (e.g., physical activity friendly school yards, food service environment [ 9 , 10 ]). Fourth, research findings from recent years suggest that determinants of NCDs such as physical inactivity [ 11 ] or overweight [ 12 ], but also mental health problems [ 13 ], can have adverse effects on school performance (e.g., grades, test scores) and thus can compromise the core mission of schools.…”
Section: Introductionmentioning
confidence: 99%